Impact of COVID-19 pandemic on ST-elevation myocardial infarction: data from two Portuguese centers. (14th October 2021) - Oliveira, L; Campante Teles, R; Machado, C; Madeira, S; Vale, N; Almeida, C; Brito, J; Leal, S; Raposo, L; Araujo Goncalves, P; Pacheco, A; Mesquita Gabriel, H; et al.
Abstract: Introduction: Recently during the COVID-19 pandemic there was a general belief in a reduction of hospital admissions due to non-infectious causes, namely cardiovascular diseases. Objectives: To evaluate the impact of the pandemic in the admissions by ST elevation acute myocardial infarction (STEMI), during the first pandemic wave. Methods: Multicentric and retrospective analysis of consecutive patients presenting in two Portuguese hospital centers with STEMI in two sequential periods – P1 (1st March to 30th April) and P2 (1st May to 30th June). A comparison of patient's clinical and hospital outcomes data was performed between the year 2020 and 2017 to 2019 for both periods. Results: A total of 347 consecutive STEMI patients were included in this study. The patient's baseline characteristics and cardiovascular risk factors were similar across the considered periods. During P1 of 2020, in comparison with previous years, a reduction in the number of STEMI patients was observed (26.0±4.2 vs 16.5±4.9 cases per month; p=0.033), contrary to what was observed during P2 (19.5±0.7 vs 20.5±0.7 cases per month; p=0.500). Percutaneous coronary interventions in the setting of failed thrombolysis were more frequent (1.9% vs 9.1%; p=0.033). A global trend in longer delays in time-key bundles of STEMI care was noted, namely pain to first medical contact, door to needle, door to wire crossing and symptoms to wire crossing times, however without statistical significance. Mortality rate was six-fold higher during P1 comparing to previous years (1.9% vs 12.1%; p=0.005), and also an increase in the number of mechanical complications (0.0% vs 3.0%; p=0.029) was observed. Conclusions: During the first COVID-19 pandemic wave there were fewer patients presenting with STEMI at catheterization laboratory for coronary angioplasty. These patients presented more mechanical complications and higher mortality rates. FUNDunding Acknowledgement: Type of funding sources: None.